Pengaruh Gaya Kepemimpinan, Motivasi Kerja terhadap Kinerja Karyawan melalui Keterlibatan Karyawan sebagai Variabel Mediasi di PT. Sunwoo Garment Indonesia - Pramudi Pangestika; I Irmawati (Prosiding University Research Colloquium, 2022)
This study discusses how leadership style and work motivation affect employee performance through employee involvement as a mediating variable at PT. Sunwoo Garment Indonesia. The purpose of this study was to examine and analyze the effect of leadership style, work motivation on employee performance through employee involvement as a mediating variable at PT. Sunwoo Garment Indonesia. The sampling technique used is the non probability sampling technique with a total of 100 respondents who are employees at PT. Sunwoo Garment Indonesia. The analytical test tool used is SmartPLS. The results of this study indicate that leadership style has a positive and insignificant effect on employee performance, leadership style has a positive and significant effect on employee engagement, work motivation has a negatif and insignificant effect on employee performance, work motivation has a positive and significant effect on employee engagement, employee engagement has a positive and significant impact on employee performance. significant on employee performance, leadership style on employee performance with employee involvement as a mediating variable shows a significant positive relationship, work motivation on employee performance with employee involvement as a mediating variable shows a significant positive relationship.